2001
DOI: 10.1097/00000542-200101000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Susceptibility to Malignant Hyperthermia in Patients with Exercise-induced Rhabdomyolysis

Abstract: Regarding these results, the authors recommend performing muscle biopsies for histologic examination and IVCT in patients with ER. In addition, the patient should be seen by a neurologist and screened for genetic abnormalities to shed light on the genetics of MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
3
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 2 publications
5
130
3
8
Order By: Relevance
“…11 Eleven out of 12 exertional rhabdomyolysis patients had abnormal in vitro pharmacological muscle test responses and three of these patients were found to have RYR1 mutations. 10 Perhaps of even greater significance, Tobin et al 12 reported the tragic case of a 12-year-old boy who survived a malignant hyperthermia reaction during anaesthesia but who subsequently died of exertional heat stroke following a game of football. DNA analysis of the child and his father revealed a mutation in the RYR1 gene that had previously been associated with malignant hyperthermia.…”
Section: Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…11 Eleven out of 12 exertional rhabdomyolysis patients had abnormal in vitro pharmacological muscle test responses and three of these patients were found to have RYR1 mutations. 10 Perhaps of even greater significance, Tobin et al 12 reported the tragic case of a 12-year-old boy who survived a malignant hyperthermia reaction during anaesthesia but who subsequently died of exertional heat stroke following a game of football. DNA analysis of the child and his father revealed a mutation in the RYR1 gene that had previously been associated with malignant hyperthermia.…”
Section: Germanymentioning
confidence: 99%
“…[7][8][9][10] These reports relate to the in vitro pharmacological muscle tests. Such findings have been reported from workers in Austria, 7 …”
mentioning
confidence: 99%
“…In some individuals MH reactions appear to be triggered by physical exercise or emotional stress. The latter observation has led to the suggestion that MH, heat stroke, and exercise-induced rhabdomyolysis might have a common denominator (2,6,7). The underlying causes of MH are abnormalities in the skeletal muscle calcium metabolism (8,9) and molecular genetic studies have mapped the primary locus of MH to chromosome 19q, the gene encoding the ryanodine receptor calcium release channel (RYR1) (2,4,10).…”
Section: Malignant Hyperthermia (Mh)mentioning
confidence: 99%
“…Such a link is plausible, considering 1) an uncontrolled rise in intracellular skeletal muscle calcium as the most important shared pathomechanism [15]; and 2) the common occurrence of MH and ERM in a number of porcine [16], equine [17] and murine [18,19] [20]. Three of these patients had RYR1 mutations but only hot-spots sequencing had been performed at the time [20]. Based on their findings, the authors recommend performing genetic testing for MH-associated RYR1 mutations, muscle biopsies for histological examination and IVCT in patients presenting with ERM.…”
Section: Ryr1-related (Exertional) Rhabdomyolysis ((E)rm)mentioning
confidence: 99%
“…Family counselling is vital to identify potentially MH-susceptible relatives [1] We performed a systematic literature review (including the patients in the studies mentioned above), based on a Pubmed search with "RYR1" and "rhabdomyolysis". This resulted in identification of several case report and small series [1,8,[21][22][23][24][25][26], and two review article [27,28] Subsequently, we also included cases from references of these articles [20,26,[29][30][31][32][33][34] and added our recent letter by Snoeck et al [35]. Finally, we added two patients from our paper on the spectrum of RYR1 related myopathies by Snoeck et al who were not included in any other publication (patients 14 and 52 [1]).…”
Section: Ryr1-related (Exertional) Rhabdomyolysis ((E)rm)mentioning
confidence: 99%